Blacklisted Password Authentication System - Payal; Sangwan, Suman; Malik, Arun (International Journal of Computer Sciences and Engineering, 2019)
Passwords have always been one of the simplest security methods, weak passwords, default passwords can easily be cracked using brute force attack and dictionary attack which is very dangerous for security of systems across the globe. Security and privacy issues are the challenges faced in many systems. Blacklisted Password Authentication System is an attempt to decrease the efficiency of Dictionary, Brute force Attack which can be implemented in any authentication system without any significant changes.